(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The focus of this paper is to design and development of a biometric enabled biometric electronic voting machine. The proposed biometric electoral voting system allows the user to scan fingerprint and iris so that his or her credentials can be compared to existing fingerprint and iris images already stored in the system’s database. Counting is going on right away, making the voting process more efficient, faster and safer. This system requires the identification of the voter Aadhaar card, the voter’s thumb impression as well as the iris image. Voter’s complete data, including all voters’ fingerprint and iris image, is collected and stored in the database. While voting, the voter gives their Aadhaar card details and puts eye in front of the iris camera and finger inside a fingerprint scanner, the system looks for the seal already provided in the data base, and then compares the iris image to authenticate the voter’s identity. If the data matches, the system commands the voter to vote through the electronic voting machine. If the fingerprints do not match, the voting presiding officer looks for the registration, or the iris image does not match after the fingerprint match, the voter is not allowed to vote, consider it vote rigging.